42. KNOWLEDGE, ATTITUDES TOWARDS CONTRACEPTIVE METHODS AMONG STUDENTS AT DAN PHUONG HIGH SCHOOL, HA NOI CITY IN 2024. (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current state of knowledge and attitudes regarding contraceptive methods among students at Dan Phuong High School, Hanoi city in 2024.Method: A cross-sectional study was conducted on 420 students at Dan Phuong High School, Dan Phuong district, Hanoi city in 2024.Results: The study found that 91.9% of students knew at least one contraceptive method. Among these, condoms (97.9%) and birth control pills (87.9%) were the most known. 86.7% of students knew the right time to use contraceptive methods. Regarding attitudes, 84.3% and 75% of students agreed that it was necessary to be equipped with knowledge about contraceptive methods and that using contraceptive methods was the best choice for adolescents. However, 42.4% of students felt it would be difficult to use contraception with their first sexual partner, and 72.8% believed that current methods still have many side effects.Conclusion: Families need to coordinate with the school to increase communication activities and health education about contraception for students to improve and develop health comprehensively.
Keywords: Knowledge; attitudes; contraceptive methods; high school students.